The lived experience of `critical moments` in Premier League academy football: A descriptive psychological phenomenological exploration - O'Halloran, L. (Liverpool John Moores University, 2019)
Events associated with change such as de-selection, injury or retirement have been referred to collectively as transitions in the sport psychology literature. The term transition suggests that these changes are rather smooth, steady and relatively easy to negotiate when in reality, such changes are often complex and deeply uncomfortable for the athlete (Nesti et al., 2012). According to Nesti and Littlewood (2011) changes that are rapid, traumatic and personal and involve new levels of self-awareness are better described as `critical moments`. A `critical moment` is defined as an event which is `…large or small, intended or unintended, and may have a positive or negative effect on a person`s sense of self` (Nesti et al., 2012). Athletic identity is often considered to be central to the experience of career transitions and `critical moments` in sport. A strong athletic identity often develops at the expense of other personal and social experiences (Brewer, 1993; Cabrita et al., 2014). As such, the athlete may become overly committed to the athlete role (Horton and Mack, 2000; Tasiemski, et al., 2004). This can affect the well-being of the athlete and may lead to inadequate coping and emotional disturbances when dealing with various setbacks (Brown and Potrac, 2009; Rongen et al., 2015). Players within an English Premier League Academy environment may be especially susceptible to experiencing `critical moments`. For instance, due to the time commitment imposed by the Elite Player Performance Plan (EPPP), it is reasonable to suggest that young players may be at risk of forgoing the exploration of various identities other than that of 'being a footballer'. This thesis explores the lived experience of `critical moments` in Premier League Academy football. This is achieved through the use of descriptive psychological phenomenology as a methodology. Despite the literature highlighting the potential benefits of employing this method within sport psychology studies (Dale, 1996; Nesti, 2004), it has not been accurately utilised in the literature to date (O`Halloran, et al., 2016). Consequently, this thesis revisits the philosophical roots of the approach in order to discuss its modification for use within the human sciences, prior to its application within sport psychology research. The subsequent study recruited 8 participants using purposive sampling. The participants were Premier League Academy Scholars aged between 16 and 18 years. For anonymity purposes, the Premier League Academy where data collection took place in this research will be referred to as ATFC. It has Category 1 status and is based in the North West of England. Data was analysed using the descriptive psychological phenomenological method devised by Giorgi (2009). The intra-structural higher-level eidetic constituents of `critical moments` that emerged from the data analysis were: emotional and psychological disturbances, psychosocial distruption/adaptation, personal growth and an altered perception of time. The findings suggest that the `lifeworld` of an ATFC Premier League Academy football player is complex. Emotional and psychological disturbances such as anxiety, uncertainty, grief and a sense of loss are experienced during `critical moments` because the individual`s identity or `structure of meaning, which is the core of their existence` is being challenged or undergoing a crisis (Hergenhahn, as cited in Nesti, 2004). Consequently, recommendations are made in this thesis towards a more holistic view of psychological/psychosocial support. For instance, from an existential perspective, angst and anxiety are considered to be a normal part of elite sport (Nesti, 2007). As such, confronting rather than attempting to remove the anxiety and discomfort experienced during a `critical moment` may become a powerful opportunity for personal growth and creating a more authentic self (Ronkainen and Nesti, 2017). Implications of this research for applied practice (i.e. accreditation pathways, practitioner development, Academy staff and the Premier League) and pedagogy (i.e. BASES and BPS accreditation programs and higher-level education) are explored in the final Chapter of this thesis.